Efektivitas Penggunaan Essential Oil Jahe Merah (Gingiber Officinale var. Rubrum) Terhadap Tingkat Kecemasan Pasien Pencabutan Gigi - Muhammad Fajrin Wijaya; Ardian Jayakusuma Amran; Rachmi Bachtiar; Andy Fairuz Z.Eva; Ayu Safirah (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Tooth extraction often triggers anxiety in patients due to the use of invasive medical instruments. Anxiety management can be addressed pharmacologically or non-pharmacologically. Aromatherapy using red ginger essential oil (Gingiber Officinale var. Rubrum) is a non-pharmacological method that has the potential to reduce anxiety effectively. This study aims to determine the effectiveness of red ginger essential oil in reducing the anxiety levels of patients undergoing tooth extraction. This quasi-experimental study employed a pretest-posttest design on 96 tooth extraction patients at RSKDGM Makassar. Anxiety levels were measured using the Modified Dental Anxiety Scale (MDAS) questionnaire before and after inhaling red ginger essential oil aromatherapy for 10 minutes. Data were analyzed using the Wilcoxon test with SPSS 26. The results showed a significant decrease in patients' anxiety levels after inhalation of red ginger essential oil aromatherapy. Before the intervention, the majority of patients had moderate anxiety (58.3%), while after the intervention, mild anxiety increased to 59.4% (p-value = 0.000). Red ginger essential oil (Gingiber Officinale var. Rubrum) is effective in reducing patients' anxiety during tooth extraction procedures.